THE IMPACT OF THE RECITATION TEACHING METHOD ON STUDENT MOTIVATION IN ELEMENTARY EDUCATION - Haifaturrahmah Haifaturrahmah; Wahyu Malajusammar; Nursina Sari (Universitas Islam Negeri Mataram, 2024)
The effect of the recitation learning method on student's motivation to learn. This study aimed to ascertain the importance of the recitation learning method's impact on the motivation of fourth-grade students at SDN 15 Mataram. The research methodology employed in this study is a quasi-experimental design, namely a non-equivalent control group design. The investigation was conducted in class IV SDN 15 Mataram, with IV A as the experimental class and IV B as the control class. The study employed a saturation sampling strategy, where 40 students were sampled from the population. Specifically, the experimental class consisted of 20 students, whereas the control class had 20 students. Data collection techniques in this study are observation, questionnaire, and documentation. Based on the results of the data analysis, it can be concluded that the results of the t-test conducted t-count are greater than those of the t-table (10.351> 2.024). Ha is accepted, and Ho is rejected, and seen from the sig value (Two-Sided p) <0.05 = (0.01 <0.05), then Ha is accepted. Ho is rejected, so as the basic rules for decision making in the independent sample T-test test can be concluded that there is an effect of the recitation learning method to increase the learning motivation of fourth-grade students of SDN 15 Mataram in the 2023/2024 school year.